Theoretical Computational of Electronic and Transport Properties and Optical Conductivity of Monolayer NiS2 under Mechanical Strain - Nguyen, Hoang Linh; Tran, The Quang; Nguyen, Minh Son; To, Toan Thang; Vuong, Van Thanh; Do, Van Truong (JST: Engineering And Technology For Sustainable Development, 2023)
In this study, the first-principle calculations using Density Functional Theory are used to evaluate the mechanical, electronic and transport properties of the NiS2 monolayer structure. The obtained results show that the monolayer structure NiS2 is broken at the tensile strain of 18% in the x direction and 14% in the y direction. The ultimate strengths are 8.0 N/m and 6.45 N/m in the x and y directions, respectively. At the ground state, the band gap is 0.49 eV with the conduction-band minimum (CBM) at the K’-Γ path and the valence-band maximum (VBM) at the Γ point. Under the strain, the energy band structure is changed and tends to become a metallic material. In addition, the effective mass, which is an important parameter related to the charged particle transportability, is also investigated. The effective mass of the electron decreases while that of the hole increases. The carrier mobility of the electron confirmed is more enhanced than that of the hole. Besides, the optical conductivity properties of NiS2 structure confirmed are pretty good. The obtained results indicate the potential of using the mechanical strain to control the electronic, optical conductivity and transport properties of the NiS2 monolayer structure in microelectromechanical and optoelectronic devices.